2016
DOI: 10.1177/1534735416669803
|View full text |Cite
|
Sign up to set email alerts
|

Boehmenan, a Lignan From the Chinese Medicinal Plant Clematis armandii, Inhibits A431 Cell Growth via Blocking p70S6/S6 Kinase Pathway

Abstract: Previously, we have shown that boehmenan, a natural product isolated from the dried stem of Caulis clematidis armandii, exhibits various biological activities. The current study investigated the effects of boehmenan on the growth of human epidermoid carcinoma A431 cells. Cell viability and 50% inhibiting concentration (IC50) were assessed by CellTiter-Glo luminescent cell viability assay. Cell cycle arrest was measured by flow cytometry. Intracellular reactive oxygen species production and mitochondrial membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…However, excess ROS production would cause severe damage to biomolecules, and then induced apoptosis and/or necrosis [27][28][29]. Additionally, previous studies also showed that lignan compounds are able to induce apoptosis through producing ROS in various cell types [30][31][32][33][34]. Thus, based on aforementioned, we speculated that ROS formation was involved in yatein-mediated cell death.…”
Section: Discussionmentioning
confidence: 79%
“…However, excess ROS production would cause severe damage to biomolecules, and then induced apoptosis and/or necrosis [27][28][29]. Additionally, previous studies also showed that lignan compounds are able to induce apoptosis through producing ROS in various cell types [30][31][32][33][34]. Thus, based on aforementioned, we speculated that ROS formation was involved in yatein-mediated cell death.…”
Section: Discussionmentioning
confidence: 79%